2021
DOI: 10.1186/s40795-021-00419-1
|View full text |Cite
|
Sign up to set email alerts
|

High food insecurity in Latinx families and associated COVID-19 infection in the Greater Bay Area, California

Abstract: Background Food insecurity impacts nearly one-in-four Latinx households in the United States and has been exacerbated by the novel coronavirus or COVID-19 pandemic. Methods We examined the impact of COVID-19 on household and child food security in three preexisting, longitudinal, Latinx urban cohorts in the San Francisco Bay Area (N = 375 households, 1875 individuals). Households were initially recruited during pregnancy and postpartum at Zuckerber… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 31 publications
3
29
0
2
Order By: Relevance
“…Similar to Escobar et al ( 2021 ), our study demonstrated low levels of food security among Latinxs during COVID‐19. Although Escobar et al ( 2021 ) did not examine documentation status in their study, they determined that level of education and employment status were associated with decreased levels of food security—two factors that are tied to documentation status.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to Escobar et al ( 2021 ), our study demonstrated low levels of food security among Latinxs during COVID‐19. Although Escobar et al ( 2021 ) did not examine documentation status in their study, they determined that level of education and employment status were associated with decreased levels of food security—two factors that are tied to documentation status.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, an underexplored construct in this link between discrimination and health is food insecurity, which can be defined as lack of access to enough food at all times for an active and healthy life. Food insecurity can be conceptualized as an indicator of vulnerability linked to intersecting social determinants of health that were impacted during the COVID‐19 pandemic (Escobar et al, 2021 ; Owens et al, 2020 ), and which are aggravated with experiences of discrimination. This includes the economic resources and/or connection to social resources that ensure adequate access to food.…”
Section: The Citizenship Shieldmentioning
confidence: 99%
“…Similarly, among the more economically heterogeneous TAB cohort, we also did not find any associations with education or income but crowding indices were also associated with intent to vaccinate against COVID-19. Paradoxically, increased housing density elevates risk for infection with SARS-Co-V2 [ 17 ], and our findings suggest that these same high-risk individuals may be less likely to get access to vaccination against COVID-19. Crowding indices may reflect immigration status, which was not collected in our survey, as previous studies have found that undocumented immigrants live in more crowded and less secure housing situations [ 24 ].…”
Section: Discussionmentioning
confidence: 92%
“…We re-contacted these cohorts telephonically in 2020 during an early period in the COVID-19 pandemic (May to September 2020) to assess food insecurity (as measured by 18 questions from the US Food Security Food Module (US HFSSM) [ 16 ]), housing conditions (including how many individuals living in a household, number of individuals sharing a bedroom and sharing a bathroom) and risk factors for COVID-19 infection (e.g. as measured by working as an essential worker during lockdown) [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The HEN and LEAD cohorts consist primarily of foreign born mothers (from Mexico and Central American countries) and were recruited primarily from ZSFG whereas TAB includes a more heterogenous mix of Latino families recruited primarily from UCSF Benioff. We re-contacted these cohorts telephonically in 2020 during an early period in the pandemic (May to September 2020) to assess food insecurity, housing conditions and risk for COVID-19 infection (Escobar et al, 2021;Mendez et al, in press).…”
Section: Latino Cohorts and Recruitmentmentioning
confidence: 99%